Effects of dietary electrolyte balance and molasses in diets with dried distillers grains with solubles on growth performance in nursery and finishing pigs - C Feoli; S M Williams; Terry L Gugle; S D Carter; N A Cole; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2007)
Two experiments were conducted to determine the effects of dietary electrolyte balance (dEB) and(or) molasses in diets with dried distillers grains with solubles (DDGS) on growth performance of nursery and finishing pigs. For Exp. 1, 126 nursery pigs (35 d old and average wt of 22.5 lb) were used with six pigs/pen and seven pens/treatment. Treatments were a corn-soybean meal-based control and diets with 30% DDGS without and with 0.93% sodium bicarbonate to adjust the dEB back to that of the control diet. Pigs fed the control diet had greater ADG (P0.58) in F/G compared to pigs fed diets with DDGS. Addition of sodium bicarbonate to nursery diets with 30% DDGS did not improve (P>0.3) growth performance. For Exp. 2, a total of 70 gilts (average wt of 196 lb) were assigned with two pigs/pen and five pens/treatment. The pigs were fed experimental diets for 26 d, a common diet for 6 d, and then reassigned to a different treatment for an additional 26-d assay. The end result was 10 pens/treatment. Treatments were a corn-soybean meal-based control and diets with 40% DDGS without and with molasses (5%) and sodium bicarbonate (none, 1, and 2%). Pigs fed the control diet had greater (P0.26), ADFI (P>0.16), or F/G (P>0.24). In conclusion, adding sodium bicarbonate and(or) molasses to diets with high inclusion of DDGS did not improve growth performance in nursery or finishing pigs.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; DDGS; Dietary electrolyte balance; Feed ingredients; Molasses